1997
DOI: 10.1007/s11665-997-0029-9
|View full text |Cite
|
Sign up to set email alerts
|

Duplex stainless steel fracture surface analysis using x-ray fractography

Abstract: The fatigue fracture surface of a duplex stainless steel was analyzed using x-ray fractography. A lower than average austenite content was observed at the fracture surface due to the transformation of austenite into deformation-induced martensite. The influence of fatigue cycling on the transformation was confined to a depth of about 30 ~tm below the fracture surface. X-ray analyses of both the ferrite-martensite and the austenite phases indicated residual stresses (Or) increasing with depth from the fracture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 6 publications
0
12
0
1
Order By: Relevance
“…In Ref. [15], fracture surface of a dual phase stainless steel used in chemical plants is investigated. Rajanna et al 16,17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ref. [15], fracture surface of a dual phase stainless steel used in chemical plants is investigated. Rajanna et al 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [15], fracture surface of a dual phase stainless steel used in chemical plants is investigated. Rajanna et al 16,17 performed XR fractographic analyses of C45 steel considering differing temperature of fracture.…”
Section: Introductionmentioning
confidence: 99%
“…Fatigue crack propagation micro‐mechanisms have only scarcely been investigated. More numerous studies deal with FCGB in hot‐ or cold‐rolled duplex stainless steels containing larger amounts of ferrite (45–62%) 14–23 . It has been shown that, in these materials, the fatigue crack growth rate (FCGR) is increasing with thermal ageing and with the amount of ferrite and with the associated embrittlement.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, the effect of ageing on crack closure in duplex stainless steels is not well established. Moreover, only RICC and TICC mechanisms have been studied 11 , 18–20 , 23 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation